Process development for maximum lycopene production from selected fruit waste and its antioxidant and antiradical activity - Jamal, Parveen; Akbar, Iqrah; Hashim, Yumi Zuhanis Has-Yun; Jaswir, Irwandi (OMICS International, 2016)
Lycopene, one of the most widely used carotenoid is an efficient antioxidant and singlet oxygen quencher. Increasing demand of lycopene in the nutraceutical and drug industry has directed the researchers to produce lycopene with cost effective methods in large scale to meet the growing demand. Thermal processing liberates this carotenoid from complexes with proteins and thus increases its bioaccessibilty. The comparison of lycopene content was explored amongst four fruit peels; guava, papaya, watermelon and red dragon fruit to choose for the best source. Lycopene content was measured using both UV–vis spectrophotometer and identified using high performance liquid chromatography (HPLC) Papaya, a tropical fruit showed tremendous potential as an alternative source and was selected to conduct further investigation. Response surface methodology (RSM) using faced centered composite design (FCCCD) was applied to study the interaction between the most contributing factors i.e., temperature, time and solid-solvent ratio with maximum lycopene yield of 103.1 mg/kg, the DPPH and FRAP equals to 81.85% and 836.46 μM Fe (II)/L respectively and a higher TPC of 1735.1 mg/L GAE at temperature 120°C, time of 5 hours in a solid-solvent ratio of 1:40 g/ ml. While lycopene yield of 74.538 mg/ kg exhibits DPPH scavenging activity of 91.14%; FRAP value of 954 μM Fe(II)/L and TPC content equals 1409.42 mg/L GAE at a temperature of 120°C for 4 hours extraction time with a solid-solvent ratio of 1:30 g/ml. The lycopene oleoresin was saponified using a mixture of propylene glycol and aqueous alkali to obtain lycopene crystals. The substantially pure lycopene crystals so obtained are fit for human consumption and were identified with High Performance Liquid Chromatography revealing that the major constituents of the lycopene oleoresin after saponification were lycopene and β-carotene which constitute 69.879% and 30.121% of the total oleoresin respectively.